Relationship Between Nurse Workload and Quality of Service in Inpatient Rooms (Oshada, 2025)
This research investigates the link between the workload of nurses and the quality of inpatient care provided. It seeks to explore how varying levels of nurse workload influence the overall standard of care in hospital wards. By utilizing a structured survey distributed to nurses, the study gathers data on workload intensity and its direct correlation with service quality metrics. Findings demonstrate a strong positive relationship between nurse workload and perceived care quality, indicating that when workloads are managed effectively, patient care quality improves. Conversely, the study reveals that excessive workloads contribute to fatigue, stress, and decreased work efficiency, which negatively impacts patient satisfaction. These results align with prior studies, which stress the need for adequate staffing levels and well-managed workloads to maintain high standards of patient care. This research enhances the understanding of nursing work dynamics, providing insights into how workload adjustments can lead to improved service outcomes. The findings also suggest potential avenues for future studies, particularly in exploring the broader impact of nurse workload on patient care and healthcare system performance.